PERANAN MAKROFAG PADA PROLIFERASI, DIFERENSIASI DAN APOPTOSIS PADA PROSES HEMATOPOISIS (PENELITIAN PADA LIMPA JANIN TIKUS DAN ASPIRAT SUMSUM TULANG MANUSIA) - Widjajanto, Edi (Jurnal Kedokteran Brawijaya, 2005)
Macrophage stimulates growth of surrounding cells by various cytokines and growth factors synthesized  and eliminate apoptotic cells by its phagocytes activity. This study was to evaluate the evidence of macrophage as regulator cells during haematopoiesis. Haematopoietic activity assessed microscopically by proportion of various haematopoietic blood cells to total nucleated blood cells on imprint preparation of fetal ratus (Wistar) spleen and human marrow aspirate, after Wright’s stain coloration. Fetal ratus spleen and human marrow aspirate were used to evaluate macrophage as a stimulator cell and suppressor cell respectively. During prenatal period, the proportion of macrophage increased at 14thdays (1.3 ± 0.9%), 16thdays (7.6 ± 1.8 %), 18thdays (12.9 ± 2.8 %) and 20thdays prenatal gestation periods (14.1 ± 3.1%). Thismacrophage increment was associated with the increase of other blood cells, except the proportion of lymphoid cell which decreased. During postnatal period the macrophage proportion decreased (11.0 ± 1.7 %), and other bloodcells proportion continuously increased except lymphoid cells which decreased. Many haematopoietic islands representing active haematopoietic process were found at 14thdays of fetal rat spleen. Macrophage in human hypocellular marrow (n = 9) increased and it exceed other blood cells proportion (29 %, p < 0.001) and contained phagocytosed apoptotic bodies. This study concludes that high macrophage regulates  haematopoiesis when it was proportionally low and regulate haematopoiesis when it was proportionally high. Keywords:Macrophage, Apoptosis, Haematopoiesis